1994
DOI: 10.1034/j.1399-3054.1994.900204.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soybean to ammonium and nitrate supplied in combination to the whole root system or separately in a split-root system

Abstract: To address the questions of whether allocation of carbohydrates to roots is influenced by ionic form of nitrogen absorbed and whether allocation of carbohydrates to roots in turn influences proportionality between NH4+ and NO3- uptake from mixed sources, NH4+ and NO3- were supplied separately to halves of a split-root hydroponic system and were supplied in combination to a whole-root system. Dry matter accumulation in the split-root system was 18% less in the NH4(+)-fed axis than in the NO3(-)-fed axis. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…This phenomenon cannot be explained by differences in kinetic properties and\or temperature dependencies between NO $ − and NH % + net uptake . From incubation experiments with constant NO $ − and varying NH % + concentrations applied simultaneously, inhibition of NO $ − net uptake in roots by NH % + has been reported in some studies (Glass, Thompson & Bordeleau, 1985 ;Lee & Drew, 1989 ;King et al, 1993 ;Chaillou et al, 1994 ;Kreuzwieser et al, 1997 ;, but few or no effects were observed in others (Smith & Thompson, 1971 ;Schrader et al, 1972 ;Oaks, Stulen & Boesel, 1979 ;Flaig & Mohr, 1992). Direct effects of NH % + on processes of NO $ − uptake have been assumed by some authors (Lee & Drew, 1989 ;King et al, 1993), whereas others have postulated that products of N assimilation such as amino compounds are responsible for the downregulation of NO $ − net uptake in roots simultaneously supplied with NH % + (Lee et al, 1992 ;Imsande & Touraine, 1994).…”
Section: Uptake Of Nitrogen By the Rootsmentioning
confidence: 99%
“…This phenomenon cannot be explained by differences in kinetic properties and\or temperature dependencies between NO $ − and NH % + net uptake . From incubation experiments with constant NO $ − and varying NH % + concentrations applied simultaneously, inhibition of NO $ − net uptake in roots by NH % + has been reported in some studies (Glass, Thompson & Bordeleau, 1985 ;Lee & Drew, 1989 ;King et al, 1993 ;Chaillou et al, 1994 ;Kreuzwieser et al, 1997 ;, but few or no effects were observed in others (Smith & Thompson, 1971 ;Schrader et al, 1972 ;Oaks, Stulen & Boesel, 1979 ;Flaig & Mohr, 1992). Direct effects of NH % + on processes of NO $ − uptake have been assumed by some authors (Lee & Drew, 1989 ;King et al, 1993), whereas others have postulated that products of N assimilation such as amino compounds are responsible for the downregulation of NO $ − net uptake in roots simultaneously supplied with NH % + (Lee et al, 1992 ;Imsande & Touraine, 1994).…”
Section: Uptake Of Nitrogen By the Rootsmentioning
confidence: 99%
“…Nitrate may be processed by booth root and leaf cells, and its accumulation in vacuoles re fl ects an important role as osmotic agent. In contrast, ammonium ions are toxic and have to be incorporated in organic compounds quickly (Chaillou et al 1994 ). Variation in metabolic processing of nitrogen sources is de fi ned by their chemical nature and diversity of plant and environmental conditions.…”
Section: Nitrogen Metabolism In Citrus Plantsmentioning
confidence: 95%
“…Conversely, it is difficult to perform similar assays with exogenous additives in crop legumes such as soybean, due to their large stature, long life cycle, the formation of a huge number of root nodules, and the requirement of soil for nodule formation. To circumvent these problems, split-root system was used in soybean to study the effects of various exogenous variable during rhizobia-legume symbioses (Chaillou, Rideout, Raper, & Morot-Gaudry, 1994;Gil-Quintana et al, 2013;Lin, Gresshoff, & Ferguson, 2012;Singleton & Bohlool, 1984). Most recently, a new split-root system was developed for continuous monitoring of soybean roots throughout the whole experiment after rhizobial infection (Hidalgo, Ruiz-Sainz, & Vinardell, 2018).…”
mentioning
confidence: 99%